2011
DOI: 10.1002/zaac.201100140
|View full text |Cite
|
Sign up to set email alerts
|

N2 Activation in NiI–NN–NiI Units: The Influence of Alkali Metal Cations and CO Reactivity

Abstract: After single electron reduction of the dinitrogen complex [L tBu Ni(μ-η 1 :η 1 -N 2 )NiL tBu ] (I) with KC 8 , reaction of the resulting compound K[L tBu Ni(μ-η 1 :η 1 -N 2 )NiL tBu ] (II) with sodium sand yields KNa[L tBu Ni(μ-η 1 :η 1 -N 2 )NiL tBu ] (1), which contains two different alkali metal ions. Treatment of I with two equivalents of sodium sand leads to the symmetric complex Na 2 [L tBu Ni(μ-η 1 :η 1 -N 2 )NiL tBu ] (2). Complexes 1 and 2 were investigated by single crystal X-ray diffraction analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 13 publications
4
61
0
1
Order By: Relevance
“…7 In addition to this mechanistic insight, it reveals that three reduced iron centers acting in a cooperative fashion make N 2 cleavage thermodynamically feasible. As summarized in Figure 9, the K + promoter stabilizes the nitride ligand of the “fixed” tri-iron-bis(nitride) isomers by about 10 kcal/mol relative to the N 2 isomers, and N-N cleavage is only favorable when an added electron and potassium are present.…”
Section: Discussionmentioning
confidence: 89%
“…7 In addition to this mechanistic insight, it reveals that three reduced iron centers acting in a cooperative fashion make N 2 cleavage thermodynamically feasible. As summarized in Figure 9, the K + promoter stabilizes the nitride ligand of the “fixed” tri-iron-bis(nitride) isomers by about 10 kcal/mol relative to the N 2 isomers, and N-N cleavage is only favorable when an added electron and potassium are present.…”
Section: Discussionmentioning
confidence: 89%
“…Investigations of analogous complexes, where one or both K + ions were replaced by Na + ions, showed that the nature of the interacting alkali metal ion does not significantly influence the activation of the NN bond. [168] Interestingly, the same β-diketiminato nickel scaffold also accommodates a variety of other nitrogenous ligands relevant to NH 3 generation, including side-on bonded N 2 H 2 , N 2 H 3 -, N 2 H 4 , and NH 3 ligands (Scheme 13). [171,172] The reaction of a nickel(II) bromide precursor with an excess of hydrazine resulted in the formation of the mononuclear hydrazido(1-) complex [L tBu Ni(η 2 -N 2 H 3 )] (53) and the concomitant precipitation of hydrazinium bromide (N 2 H 5 Br).…”
Section: Nickelmentioning
confidence: 99%
“…The next successful study on Ni-N 2 complexes was not accomplished until 2005, [166] but nickel got further into the focus of nitrogen fixation research in recent years. [167][168][169][170] A dinitrogen complex with two three-coordinate Ni I units featuring the bulky β-diketiminato ligand and an end-on bridging N 2 molecule [L tBu Ni(μ-η 1 ;η 1 -N 2 )NiL tBu ], (49) was synthesized and reported by our group in 2009. [167] Complex 49 is related to the iron complex (12) mentioned above and the subsequent publication of the corresponding Co complex (46) thus provided for the first time opportunity to compare a series of first-row late transition metal (Fe, Co, Ni) dinitrogen complexes with the same co-ligand, namely β-diketiminate.…”
Section: Nickelmentioning
confidence: 99%
“…Interestingly, the authors found that reduction of tBu LNiBr with 1.5 equiv of KC 8 results in the formation of K[ tBu LCo] 2 (μ-N 2 ), which contains a side-on interaction between the bridging N 2 and a single K + on one side [113]. Horn et al found that reacting this partially-reduced complex with sodium metal gives the mixed-alkali product NaK[ tBu LNi] 2 (μ-N 2 ) ( 40 ) [114]. Furthermore, reduction of the previously reported [ tBu LNi] 2 (μ-N 2 ) with excess sodium metal afforded the Na 2 [ tBu LNi] 2 (μ-N 2 ) species ( 41 ), completing a series of reduced Ni-N 2 species that differ only by the intercalated alkali cations.…”
Section: Effects Of Alkali Cations On N2 Activation By Transition mentioning
confidence: 99%